Plant biotechnologies: Luxembourg - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Symposium that was held in Luxembourg in June, 1989 entitled 'Plant biotechnologies for Developing Countries'. CTA cosponsored a meeting at IITA, Ibadan, Nigeria in November 1990 which addressed the more specific issue of enhancing biotechnology research